Port Access in the Lake Tanganyika : Key Challenges and Recommendations - Serrat Capdevila, Aleix; Lajaunie, Marie Laure; Bonzanigo, Laura; Figueira, Pedro; Bench, Reynaldo (World Bank, Washington, DC, 2018)
In 2016, the Republic Democratic of Congo (RDC) and Tanzania requested World Bank support for the implementation of the Lukuga project, a dam on the sole outlet of Lake Tanganyika, whose purpose was to stabilize the Lake water level in order to secure ships access to its main ports. Its main objective is to determine the relevance of the Lukuga project by assessing the ships difficulties in accessing the main ports on the Lake, characterizing impact on transport and trade, identifying the main factors hindering access to ports, and presenting a combination of measures to mitigate those factors. The study followed a mixed methods approach, combining historical data records, remote sensing estimates, satellite images, on-site measurements and data collection, and oral narratives. The report starts with a brief presentation of the Lake Tanganyika in the context of the regional trade and transport corridor. Chapter two assesses the difficulties for the ships to access the main ports in the Lake and their consequences on transport and trade. It also identifies the factors hindering access. Chapter three discusses the relevance of the proposed dam on the Lukuga river. Chapter four presents a series of measures aimed at ensuring ship access to the ports. Chapter five provides a summary of the main conclusions.